HUMANIZING ENGLISH SPEAKING SKILL USING CLT AMONG STUDENTS FROM RURAL BACKGROUND - W.T.Sheeba,J.Karthikeyan (International Journal of Advanced Science and Technology, 2020)
The rural college students in India record acutely shallow development in acquiring English language. This is due to incongruous adaptation of teaching methods in the rural classrooms. The absence of selection of appropriate method or approach in teaching the English language to the rural students has resulted in the acquisition of the language learning. Communicative Language Teaching one among the other predominant methods and approaches in language teaching that project an amicable learning environment in rural college. Communicative Language Teaching advocates the development of oral skill as the primary goal of using the target language as the means of communication. This paper suggests that Communicative Language Teaching is comparatively more beneficial to rural students than the conservative language teaching incorporated in the rural colleges. The research article also endeavours to elucidate Communicative Language Teaching as the more suitable approach in ameliorating speaking skill among rural students. The research paper outlines the advantages and propitious features Communicative Language Teaching among rural students